Specialty chemicals source book - Ash, Michael (Synapse Information Resources, 2009)
This book has been extensively revised and expanded and now contains approximately 18,000 monographs on this group of chemicals with 70,000 cross-referenced chemical synonyms, and more than 60,000 trade name equivalents.
Keywords: Chemicals.; Chemicals -- Directories.; elektronické knihy; electronic books